Odpowiedzi

2010-02-09T17:56:48+01:00
A)-(2x-2y+2xy)-(4x-2y-xy)=-2x+2y-2xy-4x+2y+xy=-6x+4y-xy
-6*2+4*(-2)-2*(-2)=-12-8+4=-16
b)6ab-(-3a+2b) +(-9ab-3a+2b)=6ab+3a-2b+(-9ab)-3a+2b=-3ab
-3*(-1)*2=6
c)-2x-(y-1)-(-x+2)-(2x-1)=-2x-y+1+x-2-2x+1=-3x-y
-3*0,1-y=-0,3-y
2010-02-09T17:56:59+01:00
A) =-2x+2y-2xy+4x+2y+xy=
=2x+4y-1xy=
=2*2+4*(-2)-1*2*(-2)=
4-8-4=-8

2010-02-09T18:00:49+01:00
A) -(2x-2y+2xy)-(4x-2y-xy)= dla x=2, y= -2
=-2x+2y-2xy-4x+2y+xy=-6x-xy+4y=-6*2-2*(-2)+4*(-2)=12+4-8=8

b) 6ab-(-3a+2b) +(-9ab-3a+2b)= dla a= -1, b=2
=6ab+3a-2b-9ab-3a+2b=-3ab=-3*(-1)*2=6

c)-2x-(y-1)-(-x+2)-(2x-1)= dla x=0,1
=-2x-y+1+x-2-2x+1=-3x-y+2=-3*0,1-y+2=-0,3-y+2=1,7-y
c)-2x-(x-1)-(-x+2)-(2x-1)= dla x=0,1
=-2x-x+1+x-2-2x+1=-4x=-4*0,1=0,4